Media servers for lighting programmers : a comprehensive guide to working with digital lighting - Claiborne, Vickie (Routledge, Taylor & Francis Group, 2021)
"Media Servers for Lighting Programmers Second Edition is the reference guide for lighting programmers working with media servers - the digital media devices used to control and manipulate video, audio, lighting, and projection content that have become the industry standard for live events, broadcast, and theatre performances. This book contains all the information you need to begin working with these devices, with topics ranging from common video terminology and equipment to the workflows for setup, patching, programming, and operating a media server from a lighting console via DMX. It also features a brief history of where this unique market originated from and offers a look at the current trends in media server technology and the growing digital media industry. This second edition also includes more information on alternative methods of programming and operating a server beyond using DMX, along with new information on projection mapping workflows, content creation software, and media management techniques. Media Servers for Lighting Programmers Second Edition is a valuable resource for the lighting programmer working in live entertainment venues. The book includes access to additional online resources and links to industry sites and articles"--